Elevated Levels of Plasma Angiogenic Factors Are Associated with Human Lymphatic Filarial Infections - Bennuru, Sasisekhar; Maldarelli, Grace; Kumaraswami, V.; Klion, Amy D.; Nutman, Thomas B. (The American journal of tropical medicine and hygiene, 2010)
Lymphatic dilatation, dysfunction, and lymphangiogenesis are hallmarks of patent lymphatic filariasis, observed even in those with subclinical microfilaremia, through processes associated, in part, by vascular endothelial growth factors (VEGFs). A panel of pro-angiogenic factors was measured in the plasma of subjects from filaria-endemic regions using multiplexed immunological assays. Compared with endemic normal control subjects, those with both subclinical microfilaremia, and those with longstanding lymphedema had significantly elevated levels of VEGF-A, VEGF-C, VEGF-D, and angiopoeitins (Ang-1/Ang-2), with only levels of basic fibroblast growth factor (bFGF) and placental growth factor (PlGF) being elevated only if lymphedema was evident. Furthermore, levels of these factors 1-year post-treatment with doxycycline were similar to pretreatment levels suggesting a minimal role, if any, for Wolbachia . Our data support the concept that filarial infection per se is associated with elevated levels of most of the known pro-angiogenic factors, with only a few being associated with the serious pathologic consequences associated with Wuchereria bancrofti infection.